Effects of acute nitric oxide precursor intake on peripheral and central fatigue during knee extensions in healthy men. Issue 7 (12th May 2019) - Le Roux‐Mallouf, Thibault; Laurent, Julien; Besset, Dimitri; Marillier, Mathieu; Larribaut, Julie; Belaidi, Elise; Corne, Christelle; Doutreleau, Stéphane; Verges, Samuel
Abstract : New Findings: What is the central question of this study ? What is the effect of acute NO precursor intake on vascular function, muscle and cerebral oxygenation and peripheral and central neuromuscular fatigue during knee‐extension exercise? What is the main finding and its importance ? Acute NO precursor ingestion increases the plasma concentrations of NO precursors (nitrate, arginine and citrulline) and enhances post‐ischaemic vasodilatation, but has no significant effect on muscle and cerebral oxygenation, peripheral and central mechanisms of neuromuscular fatigue and, consequently, does not improve exercise performance. Abstract: Nitric oxide (NO) plays an important role in matching blood flow to oxygen demand in the brain and contracting muscles during exercise. Previous studies have shown that increasing NO bioavailability can improve muscle function. The aim of this study was to assess the effect of acute NO precursor intake on muscle and cerebral oxygenation and on peripheral and central neuromuscular fatigue during exercise. In four experimental sessions, 15 healthy men performed a thigh ischaemia–reperfusion test followed by submaximal isometric knee extensions (5 s on–4 s off; 45% of maximal voluntary contraction) until task failure. In each session, subjects drank a nitrate‐rich beetroot juice containing 520 mg nitrate (N), N and citrulline (6 g; N+C), N and arginine (6 g; N+A) or a placebo (PLA). Prefrontal cortex and quadriceps near‐infrared spectroscopy parameters were monitored continuously. Transcranial magnetic stimulation and femoral nerve electrical stimulation were used to assess central and peripheral determinants of fatigue. The post‐ischaemic increase in thigh blood total haemoglobin concentration was larger in N (10.1 ± 3.7 mmol) and N+C (10.9 ± 3.3 mmol) compared with PLA (8.2 ± 2.7 mmol; P  < 0.05). Nitric oxide precursors had no significant effect on muscle and cerebral oxygenation or on peripheral and central mechanisms of neuromuscular fatigue during exercise. The total number of knee extensions did not differ between sessions (N, 71.9 ± 33.2; N+A, 73.3 ± 39.4; N+C, 74.6 ± 34.0; PLA, 71.8 ± 39.9; P  > 0.05). In contrast to the post‐ischaemic hyperaemic response, NO bioavailability in healthy subjects might not be the limiting factor for tissue perfusion and oxygenation during submaximal knee extensions to task failure. Abstract :